Rapid on-site evaluation with dynamic telecytopathology for ultrasound-guided fine-needle aspiration of head and neck nonthyroid lesions - Kamal K Khurana; Weisheng Xu; Dongliang Wang; Amar Swarnkar (Elsevier, 2015)
Background: Rapid on-site evaluation (ROSE) at the time of ultrasound-guided fine-needle aspiration (USGFNA) of head and neck lesion is essential for obtaining adequate samples and providing the preliminary diagnosis. We summarize our experience with ROSE of USGFNA on head and neck nonthyroid lesions using telecytopathology. Materials and Methods: Real-time images of Diff-Quik stained cytology smears were obtained at ultrasound suite with an Olympus DP-70 digital camera attached to an Olympus CX41 microscope, and transmitted via ethernet by a cytotechnologist to a cytopathologist in cytopathology laboratory who rendered a preliminary diagnosis. Live communication was conducted with Vocera voice communication system. The ultrasound suite was located on different floor from the cytopathology laboratory. Accuracy of ROSE via telecytopathology was compared with an equal number of cases that received ROSE, prior to introduction of telecytopathology, via conventional microscopy. Results: Rapid on-site evaluation was performed on a total of 116 USGFNA of head and neck nonthyroid lesions. The telecytopathology system and conventional microscopy was used to evaluate equal number of cases (58 each). Preliminary diagnoses of benign, atypical/suspicious for malignancy, and positive for malignancy were 72.4%, 17.2% and 10.3% for telecytopathology, and 69.0%, 10.3% and 20.7% for conventional microscopy. None of the cases were deemed unsatisfactory. The overall concordance between the preliminary and final diagnoses was 94.8% for telecytopathology and 98.3% for conventional microscopy and was not statistically significant (P = 0.309). The causes of discordant preliminary and final diagnoses were mainly attributed to availability of cell block and Papanicolaou-stained slides for review or flow cytometry results for lymphoma cases at the time of final sign out. Conclusions: Telecytopathology is comparable with conventional microscopy in ROSE of USGFNA of head and neck nonthyroid lesions.